Plant-derived synthesis of iron oxide nanoparticles for magnetic hyperthermia and magnetic resonance imaging applications - Abdelmonem, Mohamed; Soomro, Romesa; Saad, Norazalina; Ibrahim, Mohamed Ahmed; Chan, Kim Wei; Albert, Emmellie Laura; Tarmizie, Emma Ziezie; Che Abdullah, Che Azurahanim (Tsinghua University Press, 2025)
The biomedical applications of iron oxide nanoparticles (IONPs) synthesized using environmentally friendly processes are extremely promising. Using eco-friendly and nontoxic methods is a safer alternative to conventional chemical synthesis, which generates toxic byproducts. It allows for greater control over particle size and morphology. The resulting unique magnetic and optical properties of IONPs enable their use in biomedical applications such as magnetic hyperthermia (MH) and magnetic resonance imaging (MRI). This review aimed to summarize recent advances in the synthesis, characterization, and biosafety of IONPs for use in MH and MRI. It also aimed to highlight the significance of eco-friendly synthesis techniques for producing IONPs with the desired magnetic and physicochemical properties. Overall, this review elucidated the most efficient methods for utilizing iron oxide while considering biocompatibility.